Promoting Students’ Self-Regulatory Learning Skills in Online Intercultural Learning - Gerulaitiene, Egle; Mažeikienė, Natalija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The rapid growth of online distance education has implied the need to rethink delivery structures and pedagogical practices that were once appropriate (Beldarrain, 2006). Learning and teaching in a distance learning environment is a learning method that promotes interactivity, independence, and cooperation, creates favourable conditions for the students to work independently, improves accessibility of the studies, allows successfully handling work and studies and the same time, and ensures flexibility of the studies. Self-regulation is essential to the learning process. It can help students create better learning habits and strengthen their study skills, apply learning strategies to enhance academic outcomes, monitor their performance, and evaluate their academic progress (Zumbrunn et al., 2011). For students to be successful in an online course, it is necessary to work on pedagogical instruments and scenarios. The aim of the research presented in this article is to discuss the influence of online learning and pedagogical instruments and scenarios for promoting students’ self-regulatory learning skills.